Psychological Empowerment in Strengthening Women’s Human Resources in the Gig Economy Sector: A Critical Study of Female Online Motorcycle Taxi Drivers in Indonesia - Krisnoadi Triharto (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The development of the digital platform-based gig economy has created flexible work opportunities, including for female online motorcycle taxi drivers in Indonesia. However, behind this flexibility, various vulnerabilities persist, such as income uncertainty, algorithmic control, weak social protection, and complex gender-related issues. This study aims to analyse how psychological empowerment can serve as a foundation for strengthening women’s human resources in the gig economy sector, particularly among female online motorcycle taxi drivers. This study employs a qualitative approach using library research and applies critical-interpretative content analysis based on four dimensions of psychological empowerment: meaning, competence, self-determination, and impact. The findings show that female online motorcycle taxi drivers interpret their work not only as a source of livelihood, but also as a space for self-actualization and resistance against gender stigma. In terms of competence, women require multidimensional abilities, including digital literacy, navigation, service communication, occupational safety, and income management. In the self-determination dimension, the work flexibility offered by platforms is paradoxical because it remains constrained by algorithmic control, rating systems, and platform policies. Meanwhile, in the impact dimension, online motorcycle taxi work contributes to increased self-confidence, family economic contribution, and changes in social perceptions of women’s roles. Nevertheless, these positive impacts are not fully sustainable without adequate systemic support. Therefore, strengthening women’s human resources in the gig economy needs to be directed toward substantive empowerment through competence development, gender-based labour protection, platform transparency, community support, and adaptive regulation. This study contributes to shifting the perspective of women’s empowerment from merely economic empowerment toward psychological empowerment within the context of digital work.